The Crisis-Woman: Body Politics and the Modern Woman in Fascist Italy - Chang, Natasha V (Toronto Italian Studies, 2015)
Femininity in the form of the donna-crisi , or “crisis-woman,” was a fixture of fascist propaganda in the early 1930s. A uniquely Italian representation of the modern woman, she was cosmopolitan, dangerously thin, and childless, the antithesis of the fascist feminine ideal – the flashpoint for a range of anxieties that included everything from the changing social roles of urban women to the slippage of stable racial boundaries between the Italian nation and its colonies. Using a rich assortment of scientific, medical, and popular literature, Natasha V. Chang’s The Crisis-Woman examines the donna-crisi ’s position within the gendered body politics of fascist Italy. Challenging analyses of the era which treat modern and transgressive women as points of resistance to fascist power, Chang argues that the crisis-woman was an object of negativity within a gendered narrative of fascist modernity that pitted a sterile and decadent modernity against a healthy and fertile fascist one.